Analysis of Factors Influencing the Mandarin Proficiency of Ethnic Minority College Students - Xiaohua; Changlin (Lavai - International Journal of Education, 2024)
This study focuses on determining the factors that influence Mandarin proficiency of ethnic minority college students of Hulunbuir University in border minority areas of China. We used questionnaire to collect multi-dimensional data including gender, living environment, family language environment, parents’ Mandarin proficiency, parents’ academic qualifications, regional differences and parents’ occupations. Descriptive statistics, cross-contingency and chi-square tests were used to analyze the data and reveal the key factors affecting Mandarin proficiency. The results show that girls’ Mandarin proficiency is generally better than that of boys (x² = 25, p < 0.01), and students from cities and flag counties perform better in Mandarin, compared to students from rural and pastoral areas (x² = 27, p < 0.05). Family language environment(x² = 38, p < 0.01), Mandarin proficiency (x²=37, p < 0.05), occupation and academic qualifications of parents and regional background all significantly affect students' Mandarin proficiency (x 2 = 40.8, p < 0.01). Based on these findings, this study recommends the following measures to improve Mandarin education: increase investment in Mandarin education in minority areas, optimize the language learning environment, encourage parents to improve their Mandarin proficiency, and carry out more Mandarin training and practice activities in schools, while develop personalized teaching strategies for students from different backgrounds.